Menguatkan Ekonomi Informal melalui Keuangan Sosial Islam: Perspektif Prinsip Ekonomi Islam untuk Pembangunan Inklusif - Karimah, Husna; Akbariani Ahmad, Azizah; Athallah Akbar, Muhammad Ariq (Islamic Economics and Business Faculty of UIN Antasari, 2025)
The informal sector continues to dominate employment in many developing countries, including Indonesia, providing livelihoods for millions of workers who often lack access to social protection and economic security. This paper examines the origin and development of the informal economy and explores its structural determinants. Additionally, it highlights the role of Islamic economics, particularly the potential of Islamic social finance instruments—zakat, infāq, ṣadaqah, and waqf (ZISWAF)—in supporting inclusive and sustainable development within the informal sector. Employing a descriptive-qualitative approach, this study integrates content analysis, literature review, and critical analysis of both mainstream and Islamic economic perspectives. The conceptual model developed in this paper positions Islamic economic principles such as falah, maslahah, and social justice as key drivers for empowering informal sector workers. By aligning these principles with the objectives of maqāṣid al-sharī‘ah, the framework provides strategic directions for capacity building, ethical financing, and inclusive growth. The findings suggest that productive utilization of ZISWAF can facilitate the transition of informal workers toward economic resilience and formal sector integration. This study calls for collaborative engagement among government, private sector, and Islamic philanthropic institutions to ensure the realization of sustainable development goals, underpinned by ethical and spiritual commitments. Sektor informal terus mendominasi lapangan kerja di banyak negara berkembang, termasuk Indonesia, dengan menyediakan mata pencaharian bagi jutaan pekerja yang sering kali tidak memiliki akses terhadap perlindungan sosial dan jaminan ekonomi. Penelitian ini mengkaji asal-usul dan perkembangan ekonomi informal serta mengeksplorasi faktor-faktor struktural yang menjadi penentunya. Selain itu, penelitian ini menyoroti peran ekonomi Islam, khususnya potensi instrumen keuangan sosial Islam—zakat, infāq, ṣadaqah, dan wakaf (ZISWAF)—dalam mendukung pembangunan yang inklusif dan berkelanjutan di sektor informal. Melalui pendekatan deskriptif-kualitatif, studi ini mengintegrasikan analisis isi, kajian literatur, dan studi kritis terhadap perspektif ekonomi arus utama dan ekonomi Islam. Model konseptual yang dikembangkan dalam penelitian ini menempatkan prinsip-prinsip ekonomi Islam seperti falah (kesejahteraan holistik), maslahah (kemaslahatan umum), dan keadilan sosial sebagai pendorong utama dalam memberdayakan pekerja di sektor informal. Dengan menyelaraskan prinsip-prinsip tersebut dengan tujuan maqāṣid al-sharī‘ah, kerangka ini memberikan arahan strategis dalam penguatan kapasitas, pembiayaan berbasis etika, dan pertumbuhan yang inklusif. Temuan penelitian ini menunjukkan bahwa pemanfaatan ZISWAF secara produktif berpotensi memfasilitasi transisi pekerja informal menuju ketahanan ekonomi dan integrasi ke dalam sektor formal. Studi ini juga mengajak adanya kolaborasi yang sinergis antara pemerintah, sektor swasta, dan lembaga filantropi Islam guna mewujudkan tujuan pembangunan berkelanjutan yang berlandaskan komitmen etis dan spiritual.